2003
DOI: 10.1210/en.2002-220813
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Target of Endocrine Disruption in Human Luteinizing Granulosa Cells by 2,3,7,8-Tetrachlorodibenzo-p-Dioxin: Inhibition of Estradiol Secretion Due to Decreased 17α-Hydroxylase/17,20-Lyase Cytochrome P450 Expression

Abstract: Estradiol (E2) production by human luteinized granulosa cells (hLGC) is inhibited by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). The molecular target of TCDD toxicity has not been identified. The decrease in E2 is ameliorated by androgen substrate addition and is not associated with changes in aromatase cytochrome P450 (P450arom) activity or protein expression. An antihuman 17alpha-hydroxylase/17,20-lyase cytochrome P450 (P450c17) antisera and a direct radiometric assay of 17,20-lyase activity were used to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 48 publications
3
42
0
Order By: Relevance
“…Therefore, inhibition of CYP11A and CYP17 gene expression observed in this study could lead to non-selective inhibition of other cytochrome P450 enzymes and affect steroidogenesis, which could result in less synthesis of weaker androgens, such as DHEA and consequently affect production of T and E2. Inhibition of E2 secretion has been shown to be due to inhibition of CYP17 when human luteinizing granulosa cells were treated with 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) (Moran et al, 2003). Some PBDEs and their derivatives, including hydroxyl brominated diphenylethers (OH-BDEs) and methoxylated brominated diphenylethers (MeO-BDEs) can inhibit CYP17 activity in H295R cells (Cantón et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibition of CYP11A and CYP17 gene expression observed in this study could lead to non-selective inhibition of other cytochrome P450 enzymes and affect steroidogenesis, which could result in less synthesis of weaker androgens, such as DHEA and consequently affect production of T and E2. Inhibition of E2 secretion has been shown to be due to inhibition of CYP17 when human luteinizing granulosa cells were treated with 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) (Moran et al, 2003). Some PBDEs and their derivatives, including hydroxyl brominated diphenylethers (OH-BDEs) and methoxylated brominated diphenylethers (MeO-BDEs) can inhibit CYP17 activity in H295R cells (Cantón et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These reductions in A-dione and E2 levels are likely to be due to the inhibitory effects of dioxin on CYP17 and 17,20-lyase activity in the ovary rather than on aromatase activity. Indeed, Moran et al (2003) reported that the molecular target for endocrine disruption of human luteinizing granulosa cells (LGC) by dioxin was CYP17, which specifically decreases the supply of androgens for E2 synthesis, rather than aromatase. Furthermore, Li and Wang (2005) demonstrated that dioxin-like PCB126 diminished androstenedione production as well as CYP17 mRNA and 17-hydroxylase and 17,20-lyase activity (CYP17), particularly the latter, in human adrenocortical H295H cells.…”
Section: Discussionmentioning
confidence: 99%
“…The 2,4,5-T used in Vietnam was contaminated with 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) (Stellman et al 2003), the most toxic man-made substance known , which is a potent toxicant with the ability to disrupt endocrine and reproductive systems. A single dose of TCDD induces abortion and is accompanied by a decrease in serum estradiol (E2) in the macaque (Moran et al 2003). Furthermore, dioxin was found to accumulate in the adrenal glands when absorbed into the body (Li and Wang 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The 17,20-lyase specific activity of P450c17 is weak in zona fasciculata, but strong in zona reticularis in order to produce DHEA and androstenedione [26]. In the ovary, the general consensus is that only thecal cells express both the 17α-hydroxylase and 17,20-lyase activities of the P450c17 enzyme [27], although one report showed the presence of P450c17 within human cultured granulosa cells [28]. Thus, androgen formation is dependent upon the 17,20-lyase/17α-hydroxylase activities ratio.…”
Section: Steroidogenesismentioning
confidence: 99%